MRI for the Detection of Small Bowel Ischemic Injury in Arterial Acute Mesenteric Ischemia: Preclinical Study in a Porcine Model. Issue 3 (19th July 2022) - Garzelli, Lorenzo; Felli, Eric; Al‐Taher, Mahdi; Barberio, Manuel; Agnus, Vincent; Plaforet, Vincent; Bonvalet, Fanny; Baiocchini, Andrea; Nuzzo, Alexandre; Paulatto, Luisa; Vilgrain, Valérie; Gallix, Benoit; et al.
Abstract : Background: MRI is the reference for the diagnosis of arterial cerebral ischemia, but its role in acute mesenteric ischemia (AMI) is poorly known. Purpose: To assess MRI detection of early ischemic bowel lesions in a porcine model of arterial AMI. Study Type: Prospective/cohort. Animal Model: Porcine model of arterial AMI obtained by embolization of the superior mesenteric artery (seven pigs). Field Strength/Sequence: A 5‐T. T1 gradient‐echo‐weighted‐imaging (WI), half‐Fourier‐acquisition‐single‐shot‐turbo‐spin‐echo, T2 turbo‐spin‐echo, true‐fast‐imaging‐with‐steady‐precession (True‐FISP), diffusion‐weighted‐echo‐planar (DWI). Assessment: T1‐WI, T2‐WI, and DWI were performed before and continuously after embolization for 6 hours. The signal intensity (SI) of the ischemic bowel was assessed visually and quantitatively on all sequences. The apparent diffusion coefficient (ADC) was assessed. Statistical Tests: Paired Student's t‐test or Mann–Whitney U‐test, significance at P  < 0.05. Results: One pig died from non‐AMI‐related causes. The remaining pigs underwent a median 5 h53 (range 1 h24–6 h01) of ischemia. Visually, the ischemic bowel showed signal hyperintensity on DWI‐b800 after a median 85 (57–276) minutes compared to the nonischemic bowel. DWI‐b800 SI significantly increased after 2 hours (+19%) and the ADC significant decrease within the first hour (−31%). The ischemic bowel was hyperintense on precontrast T1‐WI after a median 87 (70–171) minutes with no significant quantitative changes over time ( P  = 0.46–0.93). The ischemic bowel was hyperintense on T2‐WI in three pigs with a significant SI increase on True‐FISP after 1 and 2 hours. Data Conclusion: Changes in SI and ADC can be seen early after the onset of arterial AMI with DWI. The value of T2‐WI appears to be limited. Evidence Level: 1 Technical Efficacy: Stage 2